The AfaR small RNA controls expression of the AfaD-VIII invasin in pathogenic Escherichia coli strains - Pichon, Christophe (Oxford University Press, 2013)
Pathogenic Escherichia coli strains carrying the afa-8 gene cluster are frequently associated with extra-intestinal infections in humans and animals. The afa-8 A to E genes determine the formation of an afimbrial adhesive sheath consisting of the AfaD-VIII invasin and the AfaE-VIII adhesin at the bacterial cell surface. This structure is thought to be required for host colonization. We characterized a new gene encoding the small RNA AfaR, which is transcribed in cis from the complementary strand of the 3′ untranslated region of the afaD messenger RNA, within the afaD–afaE intercistronic region. AfaR is a trans-acting Hfq-dependent antisense small RNA that binds the 5′ untranslated region of the afaD messenger RNA, initiating several ribonuclease E-dependent cleavages, thereby downregulating production of the AfaD-VIII invasin. AfaR transcription is dependent on σ(E), a member of the stress response family of extracytoplasmic alternative sigma factors. We found that the AfaR-dependent regulatory pathway was controlled by temperature, allowing the production of the AfaD-VIII invasin at temperatures above 37°C. Our findings suggest that the entry of afa-8-positive pathogenic E. coli strains into epithelial cells is tightly regulated by the AfaR small RNA.